2017
DOI: 10.5433/1679-0359.2017v38n4supl1p2719
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation height and potassium fertilization of Mulato II grass

Abstract: A pot trial in greenhouse conditions was carried out to identify at which defoliation height Mulato II grass (Urochloa hibrida cv. Mulato II) should be managed and to determine whether potassium fertilization is necessary in soil with high potassium content. The experiment was carried out in a greenhouse in a randomized block design with six treatments and five replications. Treatments consisted of a 3 × 2 factorial arrangement, with three defoliation heights (50, 65, and 80 cm) and with or without potassium m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In addition, other researchers determined that capim-açú retains high rates of leaf elongation as well as high values of leaf area for actively growing tillers when fertilized with N (Machado et al, 2013). Also, in the present study living tillers of capim-açú responded to N and K similar to mulato grass (Cabral et al, 2017), and better than palisade grass which is extensively used by farmers due to its high productivity (Sanchês et al, 2013). This supports that capim-açú could be considered as a potential alternative as forage plant to be used in the floodplain Maranhão region, Brazil, Therefore, its replacement by exotic and potentially invasive species like antelope grass (López Rosas et al, 2015) would not seem to be a good alternative.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In addition, other researchers determined that capim-açú retains high rates of leaf elongation as well as high values of leaf area for actively growing tillers when fertilized with N (Machado et al, 2013). Also, in the present study living tillers of capim-açú responded to N and K similar to mulato grass (Cabral et al, 2017), and better than palisade grass which is extensively used by farmers due to its high productivity (Sanchês et al, 2013). This supports that capim-açú could be considered as a potential alternative as forage plant to be used in the floodplain Maranhão region, Brazil, Therefore, its replacement by exotic and potentially invasive species like antelope grass (López Rosas et al, 2015) would not seem to be a good alternative.…”
Section: Resultssupporting
confidence: 68%
“…The N dose induced a quadratic effect, increasing the number of dead tillers until the dose of 78 mg dm -3 N, but values slightly decreased upon further N doses ( Figure 4C). Also, 30 mg dm -3 K 2 O caused pot -Plastic pots with 6 dm 3 and soil surface area of 0,032 m 2 ; *, ** -Significant by F test at p ≤ 0,05 and p ≤ 0,01, respectively; Means (bars) followed by distinct letter differ at p ≤ 0.05 by the Tuckey test a smaller number of dead tillers compared to the dose of 10 mg dm -3 K 2 O ( Figure 4D), probably because K stimulated the maintenance of living tillers as reported by Cabral et al (2017). Another interesting characteristic of capim-açú is the ability to maintain more living tillers than antelope grass ( Figure 4A).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…At the last cut, the residue and the root system were also collected for evaluation of mass production. Each parameter was obtained from the sum of the mass of all cuts for each grass [10].…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, in the Urochloa hybrid cv. Mulate II grass, potassium promotes more tillers and leaves production by the plant, which causes the occurance of forage accumulation (CABRAL et al, 2017). Bonfim-Silva et al (2018) observed an increase in leaves number and mass produced by Urochloa brizantha cv.…”
Section: Introductionmentioning
confidence: 99%